ANALISIS FUNGSI PRODUKSI COBB-DOUGLAS PADA KEGIATAN SEKTOR USAHA MIKRO DI LINGKUNGAN UIN SYARIF HIDAYATULLAH JAKARTA - Fitri Amalia (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2014)
The aim of this research is to acknowledge the influence of capital, worker, educational level and technology toward the production output. The data applied is a particular primary data within the data accumulation method of questionnaire consists of 7 question items. This re search is a certain population research contains of 60 respondents (business units). The method applied is OLS (Ordinary Least Square) method by applying classic assumption test and statistic test to examine the influence of independent variable to dependent one. The result obtained shows that the educational level does not have significant influence towards the production output, whereas the three other variables, which are: capital, workers, and technology does positively and significantly influence the production output. The most production factors which influence the output is the worker. Economical scale condition shows the increasing return to scale condition so that the production output still able to be increased further by increasing the input.DOI: 10.15408/sjie.v3i1.2056